A study on the relationship between Southeast Asia currencies exchange rates and Malaysian Ringgit / Khairunnisa Radzali and Nurnisreen Athyra Mohd Razak - Radzali, Khairunnisa; Mohd Razak, Nurnisreen Athyra (Faculty of Business and Management, 2013)
This paper examines relationship between Southeast Asia currencies exchange rates and Malaysian Ringgit. For that purpose, the currencies exchange rate of Singapore Dollar, Brunei Dollar, Vietnam Dong and Indonesia Rupiah were chosen to be analyzed with the Malaysian Ringgit. Simple Regression Model and Multiple Regression Model is applied to ascertain the significance relationship between Malaysian Ringgit and the Southeast Asia currency exchange rate which are Singapore Dollar, Brunei Dollar, Vietnam Dong and Indonesia Rupiah. Between the two models, Multiple Regression Model is the best fitted as model selection in this study. The result shows that there are positive relationships between the Southeast Asian currency exchange rate and Malaysian Ringgit.